Clinical characteristics and analysis of risk factors for disease progression of patients with SARS-CoV-2 Omicron variant infection: A retrospective study of 25207 cases in a Fangcang hospital - Ying-hao, Pei; Yuan-yuan, Gu; Hai-dong, Zhang; Qiu-hua, Chen; Xue-ran, Gu; Hai-qi, Zhou; Hua, Jiang (Frontiers in Cellular and Infection Microbiology, 2022)
Objectives: To summarize the clinical characteristics of COVID-19 patients infected by omicron variant of SARS-CoV-2 and explore the risk factors affecting the disease progression duration in a Fangcang hospital, Shanghai, China. Methods: A total of 25,207 COVID-19 patients infected by the omicron variant of SARS-CoV-2 were retrospectively enrolled in this study. We described the clinical characteristics and performed univariate and multivariate logistic regression analysis to identify the risk factors for non-severe to severe COVID-19 or death. Results: According to the outcomes, there were 39 severe patients (including 1 death) and 25,168 non-severe patients enrolled in this study. Among the 25,207 cases, the median age was 45 years (IQR 33-54), and 65% patients were male. Cough (44.5%) and expectoration (38.4%) were the most two common symptoms. Hypertension (10.4%) and diabetes (3.5%) were most two common comorbidities. Most patients (81.1%) were fully vaccinated. The unvaccinated and partially vaccinated patients were 15.1% and 3.9%, respectively. The length of viral shedding time (VST) was 6 days (IQR 4-9) in non-severe patients. After adjusting the confounders (age and sex), multivariate logistic regression analysis suggested that age (OR=1.039, 95%CI 1.002-1.077, p=0.038), fever (OR=2.957, 95%CI 1.329-6.576, p=0.008), cough (OR=0.296, 95%CI 0.128-0.685, p=0.004), fatigue (OR=6.770, 95%CI 2.987-15.345, p<0.001), taste disorders (OR=8.322, 95%CI 1.052-65.831, p=0.045), and comorbidity (OR=4.636, 95%CI 1.245-17.257, p=0.022) were predictors for deterioration of COVID-19. Conclusions: Non-critical patients have different clinical characteristics from critical patients. Age, fever, cough, fatigue, taste disorders, fatigue, and comorbidity are predictors for the deterioration of COVID-19 with the omicron variant of SARS-CoV-2. Cautions should be raised for patients with these risk factors.